Assessing the governance of the health policy-making process using a new governance tool: the case of Lebanon - Rasha Hamra; Sameen Siddiqi; Emma Carmel; Walid Ammar (BMC, 2020)
Abstract Background In the international agenda, it has become common to assert that the assessment of health system governance using a practical tool is crucial. This approach can help us better understand how health systems are being steered as well as to identify gaps in the decision-making process and their causes. The authors developed a new assessment tool, the Health Policymaking Governance Guidance Tool (HP-GGT), that was designed to be conceptually sound and practical. This tool enables policy-makers and stakeholders to systematically review and assess health system governance at policy-making level. This article presents first use of the HP-GGT in Lebanon, together with generated results, recommendations, and discusses how these results improve governance practices when initiating new health policy formulation processes. Methods The HP-GGT, which is a multidimensional structured tool, was used retrospectively to assess and review the process used to develop a new mental health strategy; this process was compared against consensus-based good governance principles, focusing on participation, transparency, accountability, information and responsiveness. The assessment was conducted through face-to-face interviews with 11 key informants who were involved in the development of the strategy. Results The HP-GGT enabled policy-makers to reflect on their governance practices when developing a mental health strategy and was able to identify key areas of strengths and weaknesses using good governance practice checklists given by the questions. The insights generated from the assessment equipped the national policy-makers with a better understanding of the practice and meaning of policy-making governance. Identifying weaknesses to be addressed in future attempts to develop other national health policies helped in this regard. Using the tool also increased awareness of alternative good practices among policy-makers and stakeholders. Conclusions Assessing a health policy formulation process from a governance perspective is essential for improved policy-making. The HP-GGT was able to provide a general overview and an in-depth assessment of a policy formulation process related to governance issues according to international good practices that should be applied while formulating health policies in any field. The HP-GGT was found to be a practical tool that was useful for policy-makers when used in Lebanon and awaits applications in other low- and middle-income countries to further show its validity and utility.